Effects of Clinical Pharmacology Training on Prescription Writing Skills of Interns - Hamid Noshad; Parviz Saleh (Tabriz University of Medical Sciences, 2013)
Introduction: The skill of appropriate prescription writing is a corner stone of treatment. Due to this fact, we designed a study for evaluating interns prescription writing skills after clinical pharmacology training. Methods: One hundred medical students of Tabriz University of medical science and Tabriz Azad medical university (TAMU) were chosen as intervention group and other one hundred medical students were selected as controls. Clinical pharmacology training was the intervention when the students were in internal medicine ward. Their prescribing skills were evaluated using a questionnaire. Results: Twenty eight percent of TUMS non- trained students and 68% of trained students were interested in pharmacology classes (P<0.001). Knowledge of pharmacology in non- trained TUMS students was 22% poor and 6% perfect, but in trained TUMS students it was 2% poor and 18 % perfect. In TUMS students, 80% and TAMU, 68% of the interns announced that clinical pharmacology training was essential (P= 0.25). Most of the interns had problems in correct dictation, dosage, dose adjustment of the drugs and only 4% of them had minor problems. In trained group, most of their problems solved. Conclusion: Pharmacology classes which are a part of educational curriculum during the fourth year of medical training is not enough for future clinical rotations. Clinical pharmacology training is essential for improving the prescription writing skills.